Acervo revisitado intersecções e convergências no redesign de uma coleção díspare - Jorente, Maria José Vicentini (Editora Oficina Universitária, 2021)
The book Acervo Revisitado: intersections and convergences in the redesign of a disparate collection deals with a model system of museological documentation and information created by information professionals from Unesp in Marília at the Laboratory of Research in Design and Information Retrieval - LADRI.